Optimization of Curing Conditions and Effect of Plasticizer Amount on the Mechanical and Thermal Properties of Epoxy Resin - Marzieh Sarafrazi; Ahmad Reza Ghasemi; Masood Hamadanian (علوم و تکنولوژی پلیمر, 2021)
Hypothesis: Epoxy (EP) systems, due to their unique physical and chemical properties, are one of the most widely used resins in various industries including coatings, electronic equipment and composite components in the world. Despite this widespread use, epoxies exhibit weaker toughness properties than semi-crystalline polymers due to their amorphous structure. Many factors such as the amount of softening phase, temperature, and time have a significant effect on the mechanical properties of this resin. Thus, we investigated the effect of three factors including polyurethane content (A), curing temperature (B) and time (C) on the mechanical properties and molecular structure of epoxy resin.Methods: Response surface methodology/central composite design (RSM/CCD) was used to optimize the mechanical properties of these composites. The mechanical properties such as ultimate tensile strength and elongation-at-break of the samples were obtained by tensile test. Furthermore, the thermal properties such as glass transition temperature (Tg) and storage modulus were measured by a dynamic mechanical thermal analysis (DMTA). Ultimately, a molecular dynamics simulation was used to determine the effect of annealing temperature on the interaction energy between the epoxy and polyurethane. In this respect, the chemical structure of the EP/PU composites was characterized by Fourier-transform infrared spectroscopy (FTIR), X-ray diffractometry (XRD), scanning electron microscopy (SEM), UV-Vis diffuse reflection (DRS) and thermogravimetric analysis (TGA).Findings: The results showed that the Tg and mechanical properties of EP resin strongly depended upon cure temperature and plasticizer phase. The optimal values of parameters A, B and C for maximum tensile strength were 4% by weight, 100°C and 2.4 h, respectively.